2019
DOI: 10.1111/hex.12860
|View full text |Cite
|
Sign up to set email alerts
|

End‐of‐life priorities of older adults with terminal illness and caregivers: A qualitative consultation

Abstract: Background As older adults approach the end‐of‐life (EOL), many are faced with complex decisions including whether to use medical advances to prolong life. Limited information exists on the priorities of older adults at the EOL. Objective This study aimed to explore patient and family experiences and identify factors deemed important to quality EOL care. Method A descriptive qualitative study involving three focus group discussions (n = 18) and six in‐depth interviews with older adults suffering from either a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 51 publications
(52 reference statements)
0
46
0
1
Order By: Relevance
“…The measure that is as a high priority by older patients with terminal illness, their caregivers and health care professionals is QOL . In our study QOL was reported by 2 RCTs and the effect of deprescribing on QOL was found to be inconsistent.…”
Section: Discussionmentioning
confidence: 61%
“…The measure that is as a high priority by older patients with terminal illness, their caregivers and health care professionals is QOL . In our study QOL was reported by 2 RCTs and the effect of deprescribing on QOL was found to be inconsistent.…”
Section: Discussionmentioning
confidence: 61%
“…11 In recent years, Western researches have focused on patient's values and priorities at EOL and not just on the preferences for life-sustaining treatment. [12][13][14] Since talking about death is a taboo in China, most family members and health-care providers usually avoid discussing EOL preferences to protect the feelings of the patients. 15,16 Thus, patients rarely express their EOL preferences.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of study design, nine studies exclusively reported in-depth interviews [ 13 21 ], two combined focus groups with interviews [ 22 , 23 ], one combined interviews with medical records data [ 24 ], and five conducted surveys with open-ended questions analysed using qualitative methods [ 25 29 ]. Studies included patients and/or relatives from single or combined settings in family homes (n= 6) [ 14 17 , 23 , 25 ], residential aged care (n=4) [ 16 , 22 , 24 , 26 ], hospice (n=4) [ 13 , 18 , 19 , 26 ] and hospital settings (n=3) [ 16 , 24 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients and their family/caregivers frequently mentioned the need for clinicians to alert families about the patient’s final hours [ 28 ], and be open and honest about the patient’s prognosis, with a focus on ensuring the likelihood of death was communicated clearly, without using jargon, euphemisms like ‘not doing well’, or speaking in general terms like ‘needing hospice’ [ 13 , 15 17 , 19 , 22 , 23 , 25 , 26 ]. Family members felt that straightforward and realistic information from health professionals was more valuable than encouragement to keep up hope, which caused confusion [ 19 , 26 ].…”
Section: Resultsmentioning
confidence: 99%